You Are What You Eat: Stable Isotopic Evidence Indicates That the Naticid Gastropod Neverita duplicata Is an Omnivore - Casey, Michelle M.; Fall, Leigh M.; Dietl, Gregory P. (Frontiers in Ecology and Evolution, 2016)
Species belonging to the family Naticidae (commonly called moon snails) are important infaunal gastropod predators found in soft-bottom marine communities worldwide that traditionally have been thought to prey on other mollusks, giving them the expected trophic position of a predator (trophic position = 3). Realized trophic position estimates of the naticid Neverita duplicata from Long Island Sound, however, range between 2.3 and 2.5, indicating omnivory or an anomalously low nitrogen (N) fractionation factor. To evaluate the likelihood of omnivory, this study presents whole body stable isotopic analysis of nitrogen and carbon from the soft tissues of laboratory-reared and field-collected N. duplicata. Experimental organisms were maintained on a diet of the bivalve prey Mercenaria mercenaria for one year. The median N fractionation factor derived from the experimental moon snails was 3.58 ‰ thus precluding the presence of an atypical fractionation factor (substantially lower than 3.4 ‰). Numerous molluscan taxa were collected from Long Island Sound in order to evaluate the trophic ecology of N. duplicata in the context of a natural food web. Evidence from the carbon (C) signatures of field-collected N. duplicata indicate a reliance on littoral food sources that is inconsistent with a diet of filter-feeding M. mercenaria, even when calculated using the species-specific C fractionation factor derived from the laboratory experiments. Field-collected N. duplicata also show considerable isotopic overlap (N and C) with grazing Littorina littorea. For these reasons, we hypothesize that N. duplicata feeds on some combination of benthic primary producers (most likely macroalgae and/or epiphytic diatoms), carrion, and bivalve/gastropod tissue and discuss the ecological implications of potential naticid omnivory.